Nitrogen-doped graphene self-assembled porous carbon material as well as preparation method and application thereof

A nitrogen-doped graphene self-assembled porous carbon material addresses the stacking and hydrophobicity issues of graphene sheets by forming a three-dimensional network structure, improving wettability and capacitance performance in supercapacitors.

CN119218984AActive Publication Date: 2024-12-31CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310778483.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31
Estimated Expiration
2043-06-28

AI Technical Summary

Technical Problem

Graphene sheets in supercapacitor electrodes tend to stack due to strong van der Waals forces, reducing the actual specific surface area and affecting wettability and capacitance performance, while the hydrophobic nature of carbon materials increases contact resistance.

Method used

A nitrogen-doped graphene self-assembled porous carbon material is prepared using melamine sponge as a template, where aromatic hydrocarbons form a three-dimensional network structure through carbon-nitrogen bonds, breaking π bond interactions and introducing structural nitrogen to improve wettability and capacitance.

Benefits of technology

The material exhibits high specific surface area, strong conductivity, and excellent capacitance performance with improved wettability and cycle stability, enhancing the electrochemical properties of supercapacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119218984A_ABST
    Figure CN119218984A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrode materials, and discloses a nitrogen-doped graphene self-assembled porous carbon material and a preparation method and application thereof.The preparation method comprises the steps that 1, a pretreatment solution is used for conducting dipping treatment on melamine sponge, then extrusion treatment is conducted, and the treated melamine sponge is obtained; (2) immersing the treated melamine sponge in the reaction liquid, and carrying out a reaction in a protective gas atmosphere to obtain a melamine-based graphene self-assembled precursor material; (3) carrying out carbonization treatment on the melamine-based graphene self-assembled precursor material to obtain an N-doped graphene self-assembled porous carbon material; wherein the pretreatment solution comprises a first solvent, a catalyst and optional fused salt; the reaction liquid comprises a second solvent and aromatic hydrocarbon. The nitrogen-doped graphene self-assembled porous carbon material prepared by the method is high in specific surface area, high in conductivity and good in wettability, and has excellent capacitive performance and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and more specifically, to a nitrogen-doped graphene self-assembled porous carbon material and a preparation method and application thereof. Background Art

[0002] Supercapacitors are green, safe, and efficient energy storage and conversion devices with the advantages of high power density, long cycle life, fast charge and discharge speed, high safety factor, environmental protection, and low cost. They are widely used in new energy vehicles, information and communications, aerospace, national defense science and technology, etc. Electrode materials are the core of supercapacitors and one of the important factors affecting their electrochemical performance.

[0003] In recent years, graphene has been widely used as an electrode material for supercapacitors due to its ultra-high specific surface area (2630m2g-1), high conductivity and theoretical specific capacitance (550F / g). However, the strong van der Waals forces between graphene sheets make it easy to stack and agglomerate in practical applications, resulting in its actual specific surface area (<500m2 / g) being much smaller than the theoretical value, and it is unable to fully exert its advantages as a supercapacitor electrode material. In addition, the surface of carbon materials is hydrophobic, and the wettability of electrolytes and pore surfaces is poor, which increases the contact resistance and affects the capacitance performance. Summary of the invention

[0004] The purpose of the present invention is to provide a kind of nitrogen-doped graphene self-assembled porous carbon material and its preparation method and application, by using aromatic hydrocarbon as raw material, using melamine sponge as template, by chemical bond and carbon-nitrogen bond connection in melamine sponge, polycondensation reaction occurs to generate graphene, then self-assembles into three-dimensional network structure, obtains a kind of nitrogen-doped graphene self-assembled porous carbon material after carbonization.By combining with the carbon-nitrogen bond on the surface of melamine sponge, breaking the large π bond interaction between graphene sheets, the problem that graphene materials are easy to stack can be effectively solved; rich N source is provided in melamine sponge skeleton, structural nitrogen can be introduced in graphene structure after high temperature carbonization, so as to improve the wettability of graphene porous material to electrolyte, and produce pseudocapacitive reaction in supercapacitor electrode, increase specific capacitance, improve capacitance performance.The nitrogen-doped graphene self-assembled porous carbon material prepared by the present invention has high specific surface area, strong conductivity, good wettability, and has excellent capacitance performance and cycle performance.

[0005] A first aspect of the present invention provides a method for preparing a nitrogen-doped graphene self-assembled porous carbon material, the preparation method comprising:

[0006] (1) firstly impregnating the melamine sponge with a pretreatment solution, and then extruding the melamine sponge to obtain a treated melamine sponge;

[0007] (2) immersing the treated melamine sponge in a reaction solution and reacting under a protective gas atmosphere to obtain a melamine-based graphene self-assembly precursor material;

[0008] (3) carbonizing the melamine-based graphene self-assembled precursor material to obtain an N-doped graphene self-assembled porous carbon material;

[0009] Wherein, the pretreatment solution comprises a first solvent, a catalyst and optional molten salt; and the reaction solution comprises a second solvent and aromatic hydrocarbons.

[0010] The second aspect of the present invention provides an N-doped graphene self-assembled porous carbon material prepared by the above preparation method.

[0011] The third aspect of the present invention provides the use of the above-mentioned N-doped graphene self-assembled porous carbon material as a supercapacitor electrode material.

[0012] The technical solution of the present invention has the following beneficial effects:

[0013] By combining with the carbon-nitrogen bond on the surface of melamine sponge, breaking the large π bond interaction between graphene sheets, the problem of easy stacking of graphene materials can be effectively solved; a rich N source is provided in the melamine sponge skeleton, and structural nitrogen can be introduced into the graphene structure after high-temperature carbonization, so as to improve the wettability of graphene porous materials to electrolytes, and produce pseudocapacitive reactions in supercapacitor electrodes, increase specific capacitance, and improve capacitance performance. The nitrogen-doped graphene self-assembled porous carbon material prepared by the present invention has a high specific surface area, strong conductivity, good wettability, and excellent capacitance performance and cycle performance.

[0014] By condensing raw aromatic hydrocarbons of different structural sizes into different graphene structures as self-assembly module groups, the pore structure and distribution of porous materials can be regulated.

[0015] The method of the invention is simple, the conditions are mild and controllable, and it has good industrial application prospects.

[0016] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Exemplary embodiments of the present invention will be described in more detail with reference to the accompanying drawings.

[0018] Figure 1 A scanning electron microscope image of the N-doped graphene self-assembled porous carbon material according to Example 1 of the present invention is shown.

[0019] Figure 2The Raman spectrum of the N-doped graphene self-assembled porous carbon material according to Example 1 of the present invention is shown, wherein the vertical axis represents the peak intensity, and the horizontal axis represents the wave number of the Raman spectrum.

[0020] Figure 3 The charge and discharge curves of the N-doped graphene self-assembled porous carbon material at different current densities according to Example 1 of the present invention are shown.

[0021] Figure 4 The graph showing the cycle performance of the N-doped graphene self-assembled porous carbon material according to Example 1 of the present invention is shown. DETAILED DESCRIPTION

[0022] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein.

[0023] A first aspect of the present invention provides a method for preparing a nitrogen-doped graphene self-assembled porous carbon material, the preparation method comprising:

[0024] (1) firstly impregnating the melamine sponge with a pretreatment solution, and then extruding the melamine sponge to obtain a treated melamine sponge;

[0025] (2) immersing the treated melamine sponge in a reaction solution and reacting under a protective gas atmosphere to obtain a melamine-based graphene self-assembly precursor material;

[0026] (3) carbonizing the melamine-based graphene self-assembled precursor material to obtain an N-doped graphene self-assembled porous carbon material;

[0027] Wherein, the pretreatment solution comprises a first solvent, a catalyst and optional molten salt; and the reaction solution comprises a second solvent and aromatic hydrocarbons.

[0028] In the present invention, melamine sponge is used as a template and aromatic hydrocarbons are used as raw materials. A graphene structural unit is generated by a condensation reaction connected with the template through chemical bonds, and then self-assembled into a three-dimensional network structure. After carbonization, a nitrogen-doped graphene self-assembled porous carbon material is obtained.

[0029] According to the present invention, preferably, in step (1), the immersion treatment is: immersing the melamine sponge in the pretreatment solution and stirring;

[0030] Preferably, the stirring rate is 300r / min to 900r / min, and the time is 10 to 60min;

[0031] The extrusion treatment is to squeeze out the excess pretreatment solution in the melamine sponge.

[0032] According to the present invention, preferably, step (1) can be performed multiple times, preferably 1-3 times.

[0033] According to the present invention, preferably, in step (2), the reaction temperature is 30 to 100° C. and the reaction time is 1 to 10 h;

[0034] In the present invention, preferably, in step (2), the reaction system is placed under magnetic stirring conditions, and the stirring rate is 300r / min to 900r / min.

[0035] After the reaction, the excess reaction liquid is squeezed out, washed with water, and dried to obtain the melamine-based graphene self-assembly precursor material.

[0036] According to the present invention, preferably, the catalyst is a Lewis acid, preferably including at least one of aluminum chloride, trimethylaluminum, aluminum bromide, ferric chloride, boron trichloride, antimony chloride, cupric chloride, cuprous iodide, cuprous bromide, boron trifluoride, tin tetrachloride, titanium tetrachloride and silver trifluoromethanesulfonate;

[0037] The molten salt comprises at least one of sodium chloride, sodium nitrate, sodium sulfate, barium chloride, calcium chloride, calcium sulfate, potassium chloride, potassium sulfate and potassium nitrate;

[0038] The aromatic hydrocarbon is a condensed ring aromatic hydrocarbon, preferably including at least one of naphthalene, biphenylene, methylnaphthalene, phenanthrene, pyrene, fluorene, anthracene, indene, benzopyrene, azulene, tetracene, pentacene, trinaphthalene, hexacene and heptabenzocyclopentadiene;

[0039] The first solvent and the second solvent each independently include at least one of dichloroethane, dichloromethane, chloroform, carbon tetrachloride, ethyl acetate and xylene.

[0040] In the present invention, the above aromatic hydrocarbons contain condensed ring structures, which are structural units for condensation into graphene. Under the action of a catalyst, graphene structures of different structures can be designed and regulated to synthesize, thereby providing structural units for self-assembly into porous materials with different pore structures.

[0041] In the present invention, Lewis acid catalyzes cationic polymerization of aromatic hydrocarbons followed by dehydrogenation cyclization to form a graphene structure. The reaction efficiency is low and it is difficult to obtain a large molecular weight graphene structure. The presence of molten salt can promote the conversion of the reaction, and the degree of polycondensation is higher. Polycondensation is performed on the surface of the template (melamine sponge) to form a graphene self-assembled precursor structure with a larger molecular weight.

[0042] According to the present invention, preferably, the volume ratio of the pretreatment solution, the reaction solution and the melamine sponge is 1:1-3:1;

[0043] The molar ratio of the aromatic hydrocarbon to the catalyst is 1:(0.5-5), preferably 1:(1-2);

[0044] The molar ratio of the molten salt to the aromatic hydrocarbon is (0-3):1, preferably (1.5-2):1.

[0045] According to the present invention, preferably, in the step (3), the carbonization treatment is to heat the melamine-based graphene self-assembly precursor material to 300-600° C. in a nitrogen atmosphere for carbonization for 1-3 hours, then mix it with an activator, and carbonize it at 600-900° C. for 1-5 hours to obtain a carbonized product;

[0046] Preferably, after the carbonization treatment, the carbonization product is washed with water, ultrasonically treated and dried to obtain an N-doped graphene self-assembled porous carbon material;

[0047] Preferably, the mass ratio of the melamine-based graphene self-assembly precursor material to the activator is 1:(1-3).

[0048] In the present invention, the graphene self-assembly structure in the graphene self-assembly precursor forms a connection at high temperature to obtain a three-dimensional network structure, and under the activation of an activator, more fine micropores are generated, further improving the porosity and specific surface area of ​​the material.

[0049] The molten salt appears liquid during the high-temperature process and flows between the graphene sheets to act as a separator, preventing the agglomeration of the product and the collapse of the network structure, so that the self-assembled structure of the graphene on the surface of the melamine template can be maintained. It also promotes the diffusion and activation of the activator inside the material, and produces a better synergistic effect with the activator to generate more porous structures.

[0050] The melamine sponge skeleton provides a rich source of N, which can introduce structural nitrogen into the graphene structure after high-temperature carbonization, thereby improving the wettability of the graphene porous material to the electrolyte and generating a pseudocapacitive reaction in the supercapacitor electrode, increasing the specific capacitance and improving the capacitance performance.

[0051] The second aspect of the present invention provides an N-doped graphene self-assembled porous carbon material prepared by the above preparation method.

[0052] According to the present invention, preferably, the N-doped graphene self-assembled porous carbon material is a three-dimensional network structure;

[0053] Preferably, the specific surface area of ​​the N-doped graphene self-assembled porous carbon material is 1500 m 2 / g~3070m 2 / g, the mass content of nitrogen is 1-10%, and the specific capacitance is 187F / g-357F / g at a current density of 0.05A / g.

[0054] The third aspect of the present invention provides the use of the above-mentioned N-doped graphene self-assembled porous carbon material as a supercapacitor electrode material.

[0055] The present invention is further described below by examples:

[0056] The melamine sponge used in the following examples was purchased from Henan Eric New Material Technology Co., Ltd., with a brand of RYL and a density of 8 kg / m 3 ;

[0057] In the following embodiments, the test conditions of specific capacitance at a current density of 0.05A / g are as follows: the prepared porous carbon material, carbon black, and polyvinylidene fluoride emulsion are mixed evenly in a mass ratio of 85:10:5 to form an electrode sheet with a thickness of about 0.5mm, which is placed in a vacuum oven at 120 degrees Celsius and dried for 24 hours. The electrode sheets are assembled, and a button-type supercapacitor is prepared using a 6mol / L KOH solution as an electrolyte. The electrochemical performance is tested at a current density of 0.05A / g using a blue battery test system.

[0058] In Example 1 Figure 1 The test conditions are as follows: button-type supercapacitors were prepared according to the above method, and the blue battery test system was used to test the supercapacitors under the following different current density conditions: 0.05A / g, 0.1A / g, 0.5A / g, 1A / g, and 2A / g.

[0059] Example 1

[0060] Preparation of pretreatment solution: Add 6.7 g aluminum chloride (the molar ratio of naphthalene to aluminum chloride is 1:2) and 2.9 g sodium chloride (the molar ratio of naphthalene to sodium chloride is 1:2) to 20 ml of dichloromethane, bubble nitrogen at room temperature, and stir magnetically for 0.5 h;

[0061] Preparation of reaction solution: 3.2 g naphthalene was dissolved in 20 ml dichloromethane, nitrogen was bubbled at room temperature, and magnetic stirring was performed for 0.5 h;

[0062] Step 1: put 0.16g of melamine sponge into a well-stirred pretreatment solution (the volume ratio of the pretreatment solution to the melamine sponge is 1:1), stir at 500r / min for 0.5h after it is completely immersed, and take it out; squeeze out the excess pretreatment solution until no liquid drips within 30s to obtain the treated melamine sponge.

[0063] Step 2: Immerse the treated melamine sponge in the reaction solution (the volume ratio of the reaction solution to the melamine sponge is 1:1), and react at 30°C for 6 hours under a nitrogen atmosphere and magnetic stirring at 500 r / min; take out the reacted melamine sponge, squeeze out the excess reaction solution, wash with water, and dry to obtain a melamine-based graphene self-assembly precursor material.

[0064] Step 3: Place 0.1 g of the above-mentioned melamine-based graphene self-assembly precursor material in a tubular furnace, heat it to 500°C at 10°C / min under a nitrogen atmosphere, and carbonize it for 1 hour; take it out and mix it with 0.3 g of KOH, and carbonize it at 700 degrees Celsius for 1 hour; wash the carbonized product with water, ultrasonically treat it, and dry it to obtain an N-doped graphene self-assembled porous carbon material.

[0065] The specific surface area of ​​the N-doped graphene self-assembled porous carbon material prepared in this embodiment is 2870 m 2 / g, the mass content of nitrogen is 8.1%, and the specific capacitance is 332F / g at a current density of 0.05A / g.

[0066] like Figure 1 As shown, the N-doped graphene self-assembled porous carbon material of this embodiment is a three-dimensional network structure.

[0067] like Figure 2 As shown, the Raman spectrum of the N-doped graphene self-assembled porous carbon material of the embodiment, 1350cm -1 D peak, 1600cm -1 G peak of graphene, 2600~2900cm -1 is a 2D peak.

[0068] like Figure 3 As shown, the charge and discharge curves of this embodiment at different current densities have a slightly deformed triangular shape, indicating that the battery has pseudocapacitance caused by the N groups in the graphene.

[0069] like Figure 4 As shown, the present embodiment has a cycle performance of 30,000 cycles at a current density of 1 A / g, and the capacity retention rate is above 90%.

[0070] Example 2

[0071] Preparation of pretreatment solution: 4.1 g ferric chloride (molar ratio of pyrene to ferric chloride 1:2) and 1.7 g boron trifluoride (molar ratio of pyrene to boron trifluoride 1:1) and 4.6 g sodium chloride (molar ratio of pyrene to sodium chloride 1:2) were added to 20 ml of dichloromethane, and nitrogen was bubbled into the solution at room temperature with magnetic stirring for 0.5 h;

[0072] Preparation of reaction solution: 5.1 g of pyrene was dissolved in 20 ml of dichloromethane, nitrogen was bubbled at room temperature, and magnetic stirring was performed for 0.5 h;

[0073] Step 1: put 0.16g of melamine sponge into a well-stirred pretreatment solution (the volume ratio of the pretreatment solution to the melamine sponge is 1:1), stir at 500r / min for 0.5h after it is completely immersed, and take it out; squeeze out the excess pretreatment solution until no liquid drips within 30s to obtain the treated melamine sponge.

[0074] Step 2: Immerse the treated melamine sponge in the reaction solution (the volume ratio of the reaction solution to the melamine sponge is 1:1), and react at 30°C for 6 hours under a nitrogen atmosphere and magnetic stirring at 500 r / min; take out the reacted melamine sponge, squeeze out the excess reaction solution, wash with water, and dry to obtain a melamine-based graphene self-assembly precursor material.

[0075] Step three: Place 0.1 g of the above-mentioned melamine-based graphene self-assembly precursor material in a tubular furnace, heat it to 500 ° C at 10 ° C / min under a nitrogen atmosphere, and carbonize it for 1 hour; after taking it out, mix it with 0.3 g of KOH, place it at 700 degrees Celsius for carbonization for 1 hour, and wash the carbonized product with water, ultrasonically treat it, and dry it to obtain a graphene self-assembled porous carbon material.

[0076] The specific surface area of ​​the N-doped graphene self-assembled porous carbon material prepared in this embodiment is 2650 m 2 / g, the mass content of nitrogen is 7.9%, and the specific capacitance is 302F / g at a current density of 0.05A / g.

[0077] Example 3

[0078] Preparation of pretreatment solution: 1.7 g of copper chloride (molar ratio of anthracene to copper chloride 1:0.5) and 0.41 g of potassium chloride (molar ratio of anthracene to potassium chloride 1:0.1) were added to 20 ml of dichloromethane, nitrogen was bubbled into the solution at room temperature, and magnetic stirring was performed for 0.5 h;

[0079] Preparation of reaction solution: 4.45 g anthracene was dissolved in 20 ml of dichloromethane, nitrogen was bubbled at room temperature, and magnetic stirring was performed for 0.5 h;

[0080] Step 1: put 0.16g of melamine sponge into a well-stirred pretreatment solution (the volume ratio of the pretreatment solution to the melamine sponge is 1:1), stir at 600r / min for 0.5h after it is completely immersed, and take it out; squeeze out the excess pretreatment solution until no liquid drips within 30s, to obtain the treated melamine sponge.

[0081] Step 2: Immerse the treated melamine sponge in the reaction solution (the volume ratio of the reaction solution to the melamine sponge is 1:1), and react at 60°C for 6 hours under a nitrogen atmosphere and magnetic stirring at 600 r / min; take out the reacted melamine sponge, squeeze out the excess reaction solution, wash with water, and dry to obtain a melamine-based graphene self-assembly precursor material.

[0082] Step three: Place 0.1 g of the above-mentioned melamine-based graphene self-assembly precursor material in a tubular furnace, heat it to 500 ° C at 10 ° C / min under a nitrogen atmosphere, and carbonize it for 1 hour; after taking it out, mix it with 0.3 g of KOH and carbonize it at 700 degrees Celsius for 1 hour. The carbonized product is washed with water, ultrasonically treated, and dried to obtain N-doped graphene self-assembled porous carbon material.

[0083] The specific surface area of ​​the N-doped graphene self-assembled porous carbon material prepared in this embodiment is 1506 m 2 / g, the mass content of nitrogen is 9.7%, and the specific capacitance is 287F / g at a current density of 0.05A / g.

[0084] Example 4

[0085] Preparation of pretreatment solution: 8.25 g of calcium chloride (the molar ratio of methylnaphthalene to calcium chloride is 1:3) and 16.2 g of ferric chloride (the molar ratio of methylnaphthalene to ferric chloride is 1:4) were added to 20 ml of dichloromethane, nitrogen was bubbled into the solution at room temperature, and magnetic stirring was performed for 0.5 h;

[0086] Preparation of reaction solution: 3.55 g of methylnaphthalene was dissolved in 20 ml of dichloromethane, nitrogen was bubbled at room temperature, and magnetic stirring was performed for 0.5 h;

[0087] Step 1: put 0.16g of melamine sponge into a well-stirred pretreatment solution (the volume ratio of the pretreatment solution to the melamine sponge is 1:1), stir at 600r / min for 0.5h after it is completely immersed, and take it out; squeeze out the excess pretreatment solution until no liquid drips within 30s, to obtain the treated melamine sponge.

[0088] Step 2: Immerse the treated melamine sponge in the reaction solution (the volume ratio of the reaction solution to the melamine sponge is 1:1), and react at 60°C for 6 hours under a nitrogen atmosphere and magnetic stirring at 600 r / min; take out the reacted melamine sponge, squeeze out the excess reaction solution, wash with water, and dry to obtain a melamine-based graphene self-assembly precursor material.

[0089] Step 3: Place 0.1 g of the above-mentioned melamine-based graphene self-assembly precursor material in a tubular furnace, heat it to 500°C at 10°C / min under a nitrogen atmosphere, and carbonize it for 1 hour; after taking it out, mix it with 0.3 g of KOH, and carbonize it at 700 degrees Celsius for 1 hour. The carbonized product is washed with water, ultrasonically treated, and dried to obtain N-doped graphene self-assembled porous carbon material.

[0090] According to tests, the specific surface area of ​​the N-doped graphene self-assembled porous carbon material prepared in this embodiment is 3070 m2 / g, the mass content of nitrogen is 9.1%, and the specific capacitance is 357 F / g at a current density of 0.05 A / g.

[0091] Example 5

[0092] Preparation of pretreatment solution: Add 5 g of copper chloride (the molar ratio of phenanthrene to copper chloride is 1:1.5) and 14.25 g of titanium tetrachloride (the molar ratio of phenanthrene to titanium tetrachloride is 1:3) to 20 ml of dichloromethane, bubble nitrogen at room temperature, and stir magnetically for 0.5 h;

[0093] Preparation of reaction solution: 4.45 g of phenanthrene was dissolved in 20 ml of dichloromethane, nitrogen was bubbled at room temperature, and magnetic stirring was performed for 0.5 h;

[0094] Step 1: put 0.16g of melamine sponge into a well-stirred pretreatment solution (the volume ratio of the pretreatment solution to the melamine sponge is 1:1), stir at 500r / min for 0.5h after it is completely immersed, and take it out; squeeze out the excess pretreatment solution until no liquid drips within 30s to obtain the treated melamine sponge.

[0095] Step 2: Immerse the treated melamine sponge in the reaction solution (the volume ratio of the reaction solution to the melamine sponge is 1:1), and react at 30°C for 6 hours under a nitrogen atmosphere and magnetic stirring at 500 r / min; take out the reacted melamine sponge, squeeze out the excess reaction solution, wash with water, and dry to obtain a melamine-based graphene self-assembly precursor material.

[0096] Step three: Place 0.1 g of the above-mentioned melamine-based graphene self-assembly precursor material in a tubular furnace, heat it to 500 ° C at 10 ° C / min under a nitrogen atmosphere, and carbonize it for 1 hour; after taking it out, mix it with 0.3 g of KOH and carbonize it at 700 degrees Celsius for 1 hour. The carbonized product is washed with water, ultrasonically treated, and dried to obtain N-doped graphene self-assembled porous carbon material.

[0097] The specific surface area of ​​the N-doped graphene self-assembled porous carbon material prepared in this embodiment is 2390 m 2 / g, the mass content of nitrogen is 6.7%, and the specific capacitance is 289F / g at a current density of 0.05A / g.

[0098] Example 6

[0099] Preparation of pretreatment solution: Add 6.7 g aluminum chloride (the molar ratio of naphthalene to aluminum chloride is 1:2) and 2.9 g sodium chloride (the molar ratio of naphthalene to sodium chloride is 1:2) to 20 ml of dichloromethane, bubble nitrogen at room temperature, and stir magnetically for 0.5 h;

[0100] Preparation of reaction solution: 3.2 g naphthalene was dissolved in 20 ml dichloromethane, nitrogen was bubbled at room temperature, and magnetic stirring was performed for 0.5 h;

[0101] Step 1: Put 0.1g of melamine sponge into a well-stirred pretreatment solution (the volume ratio of the pretreatment solution to the melamine sponge is 2:1), stir at 500r / min for 0.5h after it is completely immersed, and take it out; squeeze out the excess pretreatment solution until no liquid drips within 30s to obtain the treated melamine sponge.

[0102] Step 2: Immerse the treated melamine sponge in the reaction solution (the volume ratio of the reaction solution to the melamine sponge is 2:1), and react at 60°C for 10 hours under a nitrogen atmosphere and magnetic stirring at 500 r / min; take out the reacted melamine sponge, squeeze out the excess reaction solution, wash with water, and dry to obtain a melamine-based graphene self-assembly precursor material.

[0103] Step three: Place 0.1 g of the above-mentioned melamine-based graphene self-assembly precursor material in a tubular furnace, heat it to 500 ° C at 10 ° C / min under a nitrogen atmosphere, and carbonize it for 1 hour; after taking it out, mix it with 0.3 g of KOH and carbonize it at 700 degrees Celsius for 1 hour. The carbonized product is washed with water, ultrasonically treated, and dried to obtain N-doped graphene self-assembled porous carbon material.

[0104] The specific surface area of ​​the N-doped graphene self-assembled porous carbon material prepared in this embodiment is 2880 m 2 / g, the mass content of nitrogen is 7.9%, and the specific capacitance is 324F / g at a current density of 0.05A / g.

[0105] Example 7

[0106] Preparation of pretreatment solution: 6.7 g aluminum chloride (the molar ratio of naphthalene to aluminum chloride is 1:2) and 2.9 g sodium chloride (the molar ratio of naphthalene to sodium chloride is 1:2) were added to 20 ml of dichloroethane, nitrogen was bubbled into the solution at room temperature, and magnetic stirring was performed for 0.5 h;

[0107] Preparation of reaction solution: 3.2 g naphthalene was dissolved in 20 ml of dichloroethane, nitrogen was bubbled at room temperature, and magnetic stirring was performed for 0.5 h;

[0108] Step 1: Put 0.05g of melamine sponge into a well-stirred pretreatment solution (the volume ratio of the pretreatment solution to the melamine sponge is 3:1), stir at 500r / min for 0.5h after it is completely immersed, and take it out; squeeze out the excess pretreatment solution until no liquid drips within 30s to obtain the treated melamine sponge.

[0109] Step 2: Immerse the treated melamine sponge in the reaction solution (the volume ratio of the reaction solution to the melamine sponge is 3:1), and react at 30°C for 6 hours under a nitrogen atmosphere and magnetic stirring at 500 r / min; take out the reacted melamine sponge, squeeze out the excess reaction solution, wash with water, and dry to obtain a melamine-based graphene self-assembly precursor material.

[0110] Step 3: Place 0.1 g of the above-mentioned melamine-based graphene self-assembly precursor material in a tubular furnace, heat it to 500°C at 10°C / min under a nitrogen atmosphere, and carbonize it for 1 hour; after taking it out, mix it with 0.3 g of KOH, and carbonize it at 700 degrees Celsius for 1 hour. The carbonized product is washed with water, ultrasonically treated, and dried to obtain N-doped graphene self-assembled porous carbon material.

[0111] The specific surface area of ​​the N-doped graphene self-assembled porous carbon material prepared in this embodiment is 2850 m 2 / g, the mass content of nitrogen is 8.2%, and the specific capacitance is 329F / g at a current density of 0.05A / g.

[0112] Example 8

[0113] Preparation of pretreatment solution: Add 6.7 g aluminum chloride (the molar ratio of naphthalene to aluminum chloride is 1:2) and 2.9 g sodium chloride (the molar ratio of naphthalene to sodium chloride is 1:2) to 20 ml of dichloromethane, bubble nitrogen at room temperature, and stir magnetically for 0.5 h;

[0114] Preparation of reaction solution: 3.2 g naphthalene was dissolved in 20 ml dichloromethane, nitrogen was bubbled at room temperature, and magnetic stirring was performed for 0.5 h;

[0115] Step 1: put 0.16g of melamine sponge into a well-stirred pretreatment solution (the volume ratio of the pretreatment solution to the melamine sponge is 1:1), stir at 500r / min for 0.5h after it is completely immersed, and take it out; squeeze out the excess pretreatment solution until no liquid drips within 30s to obtain the treated melamine sponge.

[0116] Step 2: Immerse the treated melamine sponge in the reaction solution (the volume ratio of the reaction solution to the melamine sponge is 1:1), and react at 60°C for 10 hours under a nitrogen atmosphere and magnetic stirring at 500 r / min; take out the reacted melamine sponge, squeeze out the excess reaction solution, wash with water, and dry to obtain a melamine-based graphene self-assembly precursor material.

[0117] Step 3: Place 0.1 g of the above-mentioned melamine-based graphene self-assembly precursor material in a tubular furnace, heat it to 600°C at 10°C / min under a nitrogen atmosphere, and carbonize it for 1 hour; after taking it out, mix it with 0.3 g of KOH, and carbonize it at 900 degrees Celsius for 1 hour. The carbonized product is washed with water, ultrasonically treated, and dried to obtain N-doped graphene self-assembled porous carbon material.

[0118] The specific surface area of ​​the N-doped graphene self-assembled porous carbon material prepared in this embodiment is 2870 m 2 / g, the mass content of nitrogen is 2.3%, and the specific capacitance is 270F / g at a current density of 0.05A / g.

[0119] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A method for preparing nitrogen-doped graphene self-assembled porous carbon material, characterized in that: The preparation method comprises: (1) firstly impregnating the melamine sponge with a pretreatment solution, and then extruding the melamine sponge to obtain a treated melamine sponge; (2) immersing the treated melamine sponge in a reaction solution and reacting under a protective gas atmosphere to obtain a melamine-based graphene self-assembly precursor material; (3) carbonizing the melamine-based graphene self-assembled precursor material to obtain an N-doped graphene self-assembled porous carbon material; Wherein, the pretreatment solution comprises a first solvent, a catalyst and optional molten salt; and the reaction solution comprises a second solvent and aromatic hydrocarbons.

2. The preparation method according to claim 1, wherein In step (1), the immersion treatment comprises: immersing the melamine sponge in the pretreatment solution and stirring; Preferably, the stirring rate is 300r / min to 900r / min, and the time is 10 to 60min; The extrusion treatment is to squeeze out the excess pretreatment solution in the melamine sponge.

3. The preparation method according to claim 1, wherein Step (1) can be performed multiple times, preferably 1-3 times.

4. The preparation method according to claim 1, wherein In step (2), the reaction temperature is 30 to 100° C. and the reaction time is 1 to 10 h; After the reaction, the excess reaction liquid is squeezed out, washed with water, and dried to obtain the melamine-based graphene self-assembly precursor material.

5. The preparation method according to claim 1, wherein The catalyst is a Lewis acid, preferably comprising at least one of aluminum chloride, trimethylaluminum, aluminum bromide, ferric chloride, boron trichloride, antimony chloride, cupric chloride, cuprous iodide, cuprous bromide, boron trifluoride, tin tetrachloride, titanium tetrachloride and silver trifluoromethanesulfonate; The molten salt comprises at least one of sodium chloride, sodium nitrate, sodium sulfate, barium chloride, calcium chloride, calcium sulfate, potassium chloride, potassium sulfate and potassium nitrate; The aromatic hydrocarbon is a condensed ring aromatic hydrocarbon, preferably including at least one of naphthalene, biphenylene, methylnaphthalene, phenanthrene, pyrene, fluorene, anthracene, indene, benzopyrene, azulene, tetracene, pentacene, trinaphthalene, hexacene and heptabenzocyclopentadiene; The first solvent and the second solvent each independently include at least one of dichloroethane, dichloromethane, chloroform, carbon tetrachloride, ethyl acetate and xylene.

6. The preparation method according to claim 1, wherein The volume ratio of the pretreatment solution, the reaction solution and the melamine sponge is 1:1-3:1; The molar ratio of the aromatic hydrocarbon to the catalyst is 1:(0.5-5), preferably 1:(1-2); The molar ratio of the molten salt to the aromatic hydrocarbon is (0-3):1, preferably (1.5-2):

1.

7. The preparation method according to claim 1, wherein In the step (3), the carbonization treatment is to heat the melamine-based graphene self-assembly precursor material to 300-600° C. in a nitrogen atmosphere for carbonization for 1-3 hours, then mix it with an activator and carbonize it at 600-900° C. for 1-5 hours to obtain a carbonized product; Preferably, after the carbonization treatment, the carbonization product is washed with water, ultrasonically treated and dried to obtain an N-doped graphene self-assembled porous carbon material; Preferably, the mass ratio of the melamine-based graphene self-assembly precursor material to the activator is 1:(1-3).

8. N-doped graphene self-assembled porous carbon material prepared according to the preparation method according to any one of claims 1 to 7.

9. The N-doped graphene self-assembled porous carbon material according to claim 8, wherein: The N-doped graphene self-assembled porous carbon material is a three-dimensional network structure; Preferably, the specific surface area of ​​the N-doped graphene self-assembled porous carbon material is 1500 m 2 / g~3070m 2 / g, the mass content of nitrogen is 1-10%, and the specific capacitance is 187F / g-357F / g at a current density of 0.05A / g.

10. Use of the N-doped graphene self-assembled porous carbon material according to claim 8 or 9 as a supercapacitor electrode material.

Citation Information

Patent Citations

  • B / N-co-doped porous graphene, and preparation method and application thereof

    CN109534321A

  • Nitrogen-doped carbon nanosheet, preparation method thereof, lithium ion battery electrode, lithium ion battery and electric device

    CN110127663A

  • Preparation method of nitrogen, phosphorus and oxygen co-doped porous graphitized carbon nanosheet

    CN112479199A

  • Graphene nanobelt and preparation method thereof

    CN114735680A